Meningkatkan kreativitas siswa melalui video digital pada pembelajaran sejarah (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2022)
This classroom action research aims to increase students’ creativity through the application of Project Based Learning by making digital videos in history learning. This research has a background that comes from the findings by researchers in class XI IPS 2 SMAN 4 Depok, namely the low creativity of students in learning history, especially during the current Covid-19. Whereas creativity is one of the important aspects of skills in the 21st century that must be mastered in various aspects of life, one of which is education. This study uses a research design developed by Mc Kernan. The reason for using the Mc Kernan research design is because this research design has a flexible time, in which there are seven stages of research with two cycles and six actions taken. The results of this study indicate that students’ creativity has increased, although on the flexibility indicator, in the sub-indicator looking for suitable alternative images, students’ creativity seems to have a score that does not change in cycle I and cycle II, and on the elaboration indicator, the score decreases from cycle I to cycle II. However, a significant increase from cycle I to cycle II is seen in the flexibility indicator with sub-indicators providing new ideas for the previous design. From the results of the study, it was concluded that the application of the Project Based Learning could increase students’ creativity in learning history.
Keywords: Classroom Action Research; Project Based Learning; Creativity; Digital Video; History Learning